1995
DOI: 10.1055/s-2007-1013807
|View full text |Cite
|
Sign up to set email alerts
|

Seven Years of Experience with the Centrifugal Pump in Patients with Cardiogenic Shock

Abstract: From September 1987 to September 1994 61 patients between 29 and 78 years of age received mechanical circulatory support by means of the Biomedicus centrifugal pump. The patients were divided into three groups by indication: Group I included 15 patients with early postcardiotomy cardiogenic shock and 24 patients with late postcardiotomy cardiogenic shock. Group II 11 patients with therapy-resistant cardiogenic shock following acute myocardial infarction, and Group III 11 patients with cardiogenic shock of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…16,17 Similarly, in a report from Germany, MSOF was the major cause of death in postcardiotomy shock patients with mechanical cardiac support. 18 Just one organ system can reduce survival significantly for this patient population. For instance, in the group of patients reported by McBride et al, 100% mortality was observed for those patients who had at least one organ failure in addition to the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Similarly, in a report from Germany, MSOF was the major cause of death in postcardiotomy shock patients with mechanical cardiac support. 18 Just one organ system can reduce survival significantly for this patient population. For instance, in the group of patients reported by McBride et al, 100% mortality was observed for those patients who had at least one organ failure in addition to the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Bio-Medicus ® Centrifugal Pump and Abiomed ® device are only applied for short-term support where recovery is expected. In cases where severe cardiac damages become obvious and longterm support is indicated, the Thoratec ® , Novacor ® (Novacor Corp, Oakland, CA, USA), or HeartMate ® (Thermo Cardiosystems, Woburn, MA, USA) devices are preferred where applicable [83][84][85]88,[192][193][194][195]197,240,242,295,348,349]. In keeping with the literatures [220,230,330], however, implanting a VAD in patients having early cardiac allograft failure in order to bridge them to Re-CTx as quickly as possible has produced very disappointing results in the present study.…”
Section: Predictors Of Mortalitymentioning
confidence: 99%